2014
DOI: 10.1017/s1047951114000262
|View full text |Cite
|
Sign up to set email alerts
|

Widespread endotheliopathy in adults with cyanotic congenital heart disease

Abstract: Endothelial function is impaired in the systemic arteries and retinal vessels in adults with cyanotic congenital heart disease, suggesting a widespread endotheliopathy. Diminished numbers of endothelial progenitor cells might potentially contribute to these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…many diagnoses carry clinical manifestations of arterial vascular disease, the subclinical assessment of the pathophysiology is revealing unique abnormalities in many of the seemingly heterogeneous congenital diagnoses. [396][397][398] To date, CoA is the best-studied vascular phenotype and presents the panoply of challenges in vascular assessment and management. Individuals with CoA have endothelial dysfunction that persists despite successful repair in many individuals, including those without hypertension.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…many diagnoses carry clinical manifestations of arterial vascular disease, the subclinical assessment of the pathophysiology is revealing unique abnormalities in many of the seemingly heterogeneous congenital diagnoses. [396][397][398] To date, CoA is the best-studied vascular phenotype and presents the panoply of challenges in vascular assessment and management. Individuals with CoA have endothelial dysfunction that persists despite successful repair in many individuals, including those without hypertension.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…mediates vascular tone, hemostasis, and angiogenesis [9,10]. The majority of [10][11][12][13][14], although not all [15], studies in the literature to date, show that endothelium function in cyanotic CHD patients assessed by flow-mediated distensibility is impaired. It is postulated to be related to disturbed production of endothelialderived nitric oxide, an important regulator of smooth muscle cell relaxation, and has a pathognomonic relation with increased arterial wall stiffness.…”
mentioning
confidence: 99%
“…The results available in the literature on the microvascular endothelial function of ACHD are conflicting. Cordina et al evaluated the vascular reactivity of individuals with cyanotic congenital heart disease and reported the presence of endothelial dysfunction when patients were evaluated for flow‐mediated dilatation but not for peripheral arterial tonometry (PAT), suggesting the presence of endothelial dysfunction in conductance vessels but not in the microcirculation . Lambert et al used the PAT technique and observed microvascular endothelial dysfunction in patients with Fontan circulation .…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 4 Microvascular data and arterial blood pressure of healthy volunteers (CONTROL, n = 29) and adult patients with congenital heart disease (ACHD, n = 31 for ACh and PORH data; n = 24 for SNP data) patients were evaluated for flow-mediated dilatation but not for peripheral arterial tonometry (PAT), suggesting the presence of endothelial dysfunction in conductance vessels but not in the microcirculation. 24 Lambert et al used the PAT technique and observed microvascular endothelial dysfunction in patients with Fontan circulation. 26 Oechslin et al employed venous occlusion plethysmography and observed the occurrence of microvascular endothelial dysfunction in cyanotic congenital cardiopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation